Pengembangan Pemasaran Digital Oleh-Oleh Khas Medan: Strategi Peningkatan Ekonomi Berbasis Kearifan Lokal di Rumah Markisa Noerlen - Solahuddin Nasution; Yudhistira Adhitya Pratama; Syafrita Ridha Ginting; Agung Pratama (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Rumah Markisa Noerlen, which has been a producer of traditional passion fruit syrup since 1985, now faces serious challenges in the form of market decline due to the impact of the Covid-19 pandemic, compounded by suboptimal digital marketing. Therefore, this community service aims to develop a local wisdom-based digital marketing strategy, expected to enhance the visibility and competitiveness of Rumah Markisa Noerlen's products in an increasingly competitive market. The method used is Participatory Action Research (PAR), which includes observation, interviews, training, and mentoring in digital content management, as well as website development as a promotional and sales platform. The results show an improvement in partners' capabilities in producing digital content, managing websites, and creating attractive promotional materials. The discussion highlights the importance of integrating local cultural values into digital marketing as a competitive advantage, as well as the collaboration between academics and MSME actors in technology adaptation. The next planned achievements include the utilization of data analytics, continuous training, and expanding networks with tourism communities to support business development and strengthen the local economy. This approach is expected to provide innovative solutions for the cultural-based MSME development in Medan City, benefiting not only the entrepreneurs but also the community as a whole.